Diasporic Alienation and Empathy in Arab-American Poetry: A Postcolonial Comparative Study of Khalil Gibran and Suheir Hammad - Aldrian, Aldrian; Lestari, Septi; Fitriani, Laily (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This research explores themes of diasporic alienation and empathy in Khalil Gibran and Suheir Hammad’s poetry from a postcolonial perspective. Khalil Gibran, a Lebanese-American poet, and Suheir Hammad, a Palestinian-American poet, articulate their complex diasporic experiences from distinct historical moments. Both emphasize a persistent longing to reconnect with their homelands, revealing how alienation and empathy shape identity in diaspora. While numerous studies have analyzed Arab-American literary expressions of identity and displacement, there remains a notable scholarly gap concerning how hybridity and subalternity shed light on the poetry of these two prominent poets. Employing postcolonial theories of hybridity and subalternity, this research uses a descriptive qualitative method, analyzing primary data from Gibran’s poem “Dead Are My People” and Hammad’s poems “Break (Rebirth)”, “Break (Sister)”, and “Break (Embargo)”. Secondary sources include literature addressing Arab-American diasporic experiences, the Israel-Gaza conflict, and the Lebanese famine events. Through textual and contextual analyses, the findings reveal Gibran’s depiction of geographical and cultural alienation, emotional alienation, and alienation from collective solidarity, whereas Hammad primarily explores identity alienation. Regarding empathy, Gibran addresses the historical trauma of the Lebanese famine under Ottoman rule, while Hammad reflects on the contemporary violence and suffering in Palestine. This study contributes to Arab-American literary scholarship by showing how diasporic alienation and empathy illuminate ongoing colonial impacts and identity negotiation across generations.